2020
DOI: 10.1038/s42003-020-01126-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural effects of the highly protective V127 polymorphism on human prion protein

Abstract: Prion diseases, a group of incurable, lethal neurodegenerative disorders of mammals including humans, are caused by prions, assemblies of misfolded host prion protein (PrP). A single point mutation (G127V) in human PrP prevents prion disease, however the structural basis for its protective effect remains unknown. Here we show that the mutation alters and constrains the PrP backbone conformation preceding the PrP β-sheet, stabilising PrP dimer interactions by increasing intermolecular hydrogen bonding. It also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 90 publications
(187 reference statements)
0
11
0
Order By: Relevance
“…For example, Y218 and S222 with M166, and I215 and Y218 with Q172. Perturbation of the dynamics of the β2-α2 loop has previously been shown to affect the dynamics of the C-terminus of helix 3 (47), and in PrP 137 the loss of the CHR and contacts with the β-sheet appear to have propagated beyond the immediate site of the truncation. In addition, the C-terminus of helix 1 and following residues (residues 153-158) also display an increased level of flexibility (Fig.…”
Section: Structural Perturbations In Prp 137 Resulting From Loss Of Chrmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Y218 and S222 with M166, and I215 and Y218 with Q172. Perturbation of the dynamics of the β2-α2 loop has previously been shown to affect the dynamics of the C-terminus of helix 3 (47), and in PrP 137 the loss of the CHR and contacts with the β-sheet appear to have propagated beyond the immediate site of the truncation. In addition, the C-terminus of helix 1 and following residues (residues 153-158) also display an increased level of flexibility (Fig.…”
Section: Structural Perturbations In Prp 137 Resulting From Loss Of Chrmentioning
confidence: 99%
“…The helical regions of PrP variants exhibit S 2 values of 0.8 – 0.9, typical of structured regions of folded proteins. Residues of the α2–α3 loop (residues 194–199) and the C-terminus of helix 3 display reduced S 2 values, reflecting increased flexibility, commonly observed in loop regions of globular proteins (46, 47). The reduction in S 2 for residues 164-168 in PrP 137 would suggest that the β2-α2 loop is more flexible in PrP 137 than PrP 119 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies investigating the polymorphism at position 129 generally used a shorter construct of huPrP, lacking the unstructured N-terminal domain [28,29]. To test the effect of the unstructured N-terminal domain on aggregation kinetics and oligomer formation, we compared a shorter construct of the 129M variant without the N-terminal half, huPrP(121-230), to our full-length proteins (Figure 3).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In vitro studies demonstrated that flexible and unstructured N-terminal regions of PrP have an intrinsic tendency to form homodimers and are involved in dimerization interface of PrP [76,100]. In the lack of these interactions mediated by the 23-118 N-terminal tail, the destabilizing effects of G127V mutation are not evident in the in vitro experiments [99]. In contrast, the N-terminal PrP fragment has been reported to be involved in interactions with cellular partners,which may restrict its conformation and thus may be responsible also for the apparent absence of the destabilizing effect of the V127 mutation on PrP dimers in cellulo.…”
Section: Discussionmentioning
confidence: 94%
“…119-231, PrP fragment devoid of 23-118 region) inhibiting prion propagation, arguing that the G127V mutation alters the backbone conformation preceding the ß-sheet of the protein enhancing the intermolecular hydrogen bonding, which facilitates stablization of PrP dimers, inhibiting in turn the prion propagation [99]. In vitro studies demonstrated that flexible and unstructured N-terminal regions of PrP have an intrinsic tendency to form homodimers and are involved in dimerization interface of PrP [76,100].…”
Section: Discussionmentioning
confidence: 99%